Cooperative Ni/Cu‐Catalyzed Asymmetric Propargylic Alkylation of Aldimine Esters. Issue 34 (1st July 2020) - Peng, Lingzi; He, Zhuozhuo; Xu, Xianghong; Guo, Chang
Abstract: A novel Ni/Cu dual catalysis gives rise to fundamentally new cooperative reactivity and enables the regio‐ and enantioselective propargylic alkylation reaction. A diverse set of α‐quaternary propargylated amino ester derivatives were synthesized in good yields with excellent enantioselectivity (up to 99 % ee ). This work highlights the power of cooperative catalysis, which can be expected to have broad implications in homogeneous catalysis beyond the highly valuable synthetic intermediates. Abstract : It takes two : A highly efficient propargylic alkylation reaction was developed that delivers high yields with excellent enantiomeric ratios through dual Ni/Cu catalysis (up to 99 % ee ). This Ni/Cu bimetallic system provides a reliable and a versatile approach for the development of a wide range of useful stereocontrolled reactions.